2017
DOI: 10.1001/jamainternmed.2017.0453
|View full text |Cite
|
Sign up to set email alerts
|

Physician Breast Cancer Screening Recommendations Following Guideline Changes

Abstract: Different professional societies and organizations continue to disagree over the optimal time to initiate and discontinue breast cancer screening mammography and the optimal screening interval. In October 2015, the American Cancer Society (ACS) revised its guidelines, encouraging personalized screening decisions for women ages 40 to 44 years followed by annual screening starting at age 45 years and biennial screening for women 55 years or older. 1 The US Preventive Services Task Force (USPSTF) reissued its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 5 publications
2
43
0
2
Order By: Relevance
“…We found that participants reiterated their beliefs and feelings of commitment to undergoing breast cancer screening, which may be in conflict with current guidelines. Thus, physicians may benefit from strategies that provide a way to discuss guidelines with patients as a way to implement current clinical guidelines into practice . This may be addressed by engaging women in a tailored strategy that incorporates their personal values and beliefs as they assess the benefits and downsides of continuing breast cancer screening as they age .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that participants reiterated their beliefs and feelings of commitment to undergoing breast cancer screening, which may be in conflict with current guidelines. Thus, physicians may benefit from strategies that provide a way to discuss guidelines with patients as a way to implement current clinical guidelines into practice . This may be addressed by engaging women in a tailored strategy that incorporates their personal values and beliefs as they assess the benefits and downsides of continuing breast cancer screening as they age .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, physicians may benefit from strategies that provide a way to discuss guidelines with patients as a way to implement current clinical guidelines into practice. 31,32 This may be addressed by engaging women in a tailored strategy that incorporates their personal values and beliefs as they assess the benefits and downsides of continuing breast cancer screening as they age. 18 Using a shared decision making strategy can allow women to discuss their values and to weigh the complex tradeoffs between different, viable options.…”
Section: Discussionmentioning
confidence: 99%
“…Further, population estimates were for women aged 45‐74, the age category available in ACS that is most congruent with recommended screening ages. However, many women who utilize screening are younger or older than the recommended screening age . Thus, the population estimates used are representative of theoretical demand, not practical demand.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…However, many women who utilize screening are younger or older than the recommended screening age. 37 Thus, the population estimates used are representative of theoretical demand, not practical demand.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…These practical challenges may make it easier to simply order routine screening mammograms for women in their 40s, as many primary care physicians do. 1 Expanded use of decision tools, which could be used by patients at home or in office waiting rooms, could help to improve the quality of the information shared with patients and make shared decision making more efficient and feasible. Research demonstrates that such tools can increase knowledge and decrease decisional conflict and anxiety; in some cases, they also influence uptake of screening.…”
Section: Supplemental Contentmentioning
confidence: 99%